Properties of Carbon Black from Jatropha Seed Shell as A Potential Source of Filler Enhancement in Biocomposites - N. A. Sri Aprilia; H.P.S. Abdul Khalil; Amri Amin (International Journal of Science and Engineering, 2016)
The use of biomass as filler in biocomposites are becoming widespread in the present decade because its variety of advantages. Jatropha (jatropha curcas L) seed shell after separated from kernel can be used to produce carbon black because of its higher carbon content, and have the potentiality to use as reinforcement in composites. In this study, carbon black was produced from jatropha seed shell by carbonization in furnace method  for 1 hour at 600oC. Thermo gravimetric analysis to analyze seed shell of jatropha as raw material. The morphological properties of the carbon black were analyzed by elemental analysis by X-ray (EDX), SEM, TEM,  XRD, SEM, and TEM.  It was found that the yield of carbon black was 40% which included 4 different sizes ranging from 70 – 300 mesh in distribution of particle size analysis. Carbon black suggested that it could be a good filler or reinforcement in biocomposites